Characterization of carbon anode constituents under CO2 gasification: A try to understand the dusting phenomenon. (15th September 2015) - Chevarin, F.; Lemieux, L.; Picard, D.; Ziegler, D.; Fafard, M.; Alamdari, H.
Abstract: Carbon anodes, used in Hall–Héroult electrolysis process, are subject to carboxy gasification. It is generally thought that the baked pitch of anode is more chemically reactive than coke and thus it preferentially reacts with CO2, resulting in premature disintegration of anode. In this study, the apparent reaction rates of anode and its constituents (coke, pitch and butt) were measured separately. The reaction conditions were set to minimize the mass transport limitations (sample size: 2 mg, CO2 flow rate: 100 ml/min and particle size: about 30 μm). The activation energies of anode, coke, pitch and butt were found to be 192, 175, 207 and 182 kJ/mol, respectively. The evolution of specific surface areas in micro-, meso- and macropores as a function of gasification percentage was revealed using CO2 and N2 adsorptions and the ratio of catalyst/inhibitor was obtained using XPS analysis. It was found that the apparent reaction rate of anode and its constituents increased with the progress of the gasification under CO2 atmosphere at 960 °C. The reaction rate of 0.033 min −1 at 50% of gasification, was obtained for pitch, which is similar to those of anode, coke and butt, suggesting that a pitch, baked separately, is not the most reactive constituent of anode.